Improved radiation characteristic of balanced antipodal vivaldi antenna in array configuration - Shaikh, Faraz Ahmed; Khan, Sheroz; Abdul Rahman, Farah Diyana; Yusoff, Siti Hajar; Alam, A. H. M. Zahirul; Badron, Khairayu; Shahid, Zeeshan (2018)
H-plane array configuration of different elements of balance antipodal Vivaldi antenna is presented in this paper. The configuration of an antenna is based on the improvement in radiation characteristics of BAVA. The use of two and four elements placed in h-plane configuration is considered. Each single element antenna is printed on FR4 substrate of 1.5 mm thickness with relative permittivity of 4.3. The dimension of each single element is 60.75 mm × 66 mm approximately. The single element of BAVA covers almost whole Ultra-wide band frequency range with -10dB of return loss and an antenna works well at 9GHz frequency with maximum bandwidth of 1.186 GHz and respectable gain of 11.3 dBi. The elliptical shaped dielectric director with permittivity similar to that of FR4 substrate is implanted in an antenna aperture in order to intensify the radiation pattern with low side lobe level and improved gain of an antenna. In h-plane configuration the two and four elements of antenna will be compared with modified version of BAVA. The extensions in length of a substrate called director significantly enhance the radiation characteristics. The design and optimization development is proven viable via CST simulation software.